Implementasi Strategi Marketing Mix di Sekolah Tinggi Ilmu Tarbiyah Tihamah Cirebon - Abidin, Zainal; Hamzah, Akhmad Fauzi (Jurnal Inovatif Manajemen Pendidikan Islam, 2024)
institution. Internal school analysis is the main basis for designing an effective marketing strategy, which must provide a comprehensive picture of the steps that will be taken by the institution. This research is qualitative research that explores and understands processes and contexts in the field, using STIT Tihamah Cirebon as the main data source. Data was collected through observation, interviews and documentation. STIT Tihamah Cirebon has succeeded in implementing the 7 components in the Marketing Mix effectively, starting from superior products in the form of Al-Quran and hadith memorization programs, affordable prices with ease of payment, strategic locations that support accessibility, promotions through various media, quality human resources with leading lecturers, complete campus facilities, and a continuous and tiered education process.